ChemInform Abstract: Exploration of New Superconductors and Functional Materials, and Fabrication of Superconducting Tapes and Wires of Iron Pnictides. Issue 51 (December 2015) - Hosono, Hideo; Tanabe, Keiichi; Takayama‐Muromachi, Eiji; Kageyama, Hiroshi; Yamanaka, Shoji; Kumakura, Hiroaki; Nohara, Minoru; Hiramatsu, Hidenori; Fujitsu, Satoru
Abstract: Review: [highlights of a research project supported by the Japanese Government; 535 ref]